Pemenuhan Keadilan Dalam Sistem Hukum Pidana Indonesia Melalui Tugas LPSK - Djamaludin, Djamaludin; Arrasyid, Yanuriasnyah (Jurnal Ilmu Hukum Kyadiren, 2024)
The LPSK (Witness and Victim Protection Agency) is an institution tasked with safeguarding the rights of witnesses and victims within the framework of the Indonesian criminal justice system to ensure justice and security. However, the implementation of witness and victim protection faces challenges such as a lack of understanding among law enforcement officers, insufficient resources and facilities, and intimidation against witnesses and victims. Therefore, an analysis of the implementation of witness and victim protection becomes crucial to identify solutions and enhance the Indonesian criminal justice system. Through continuous collaboration and efforts, it is expected that the protection of witnesses and victims can be improved, thereby increasing public trust in the Indonesian criminal justice system.